Design of West Java MSME Center Neo Vernacular Architecture Concept - Abdul Gani Alfarizi; Andiyan Andiyan; Husna Izzati (Jurnal Arsitektur Archicentre, 2023)
Micro, small and medium enterprises are one of the potential drivers of the economy and absorb a lot of labor. MSMEs in Indonesia continues to grow and develop with a lot of government support for business actors. West Java has a variety of quality MSME products with great market potential that require a space that functions as a place for the development and sale of MSME products, this is what underlies the design of the West Java MSME Center. The design of the West Java MSME Center uses the Neo Vernacular Architecture design approach as an effort to represent architectural values, philosophy, and Sundanese culture in the building. This design is carried out by searching for literature, precedent studies, and comparative studies related to the title and theme of the design and then united with the results of analysis and concepts to create buildings that are under the objectives and themes of design. The design of this UMKM Center is expected to be useful and can be developed again in the future.